Surgical resection of glioblastomas induces pleiotrophin-mediated self-renewal of glioblastoma stem cells in recurrent tumors. Issue 7 (29th December 2021) - Knudsen, Arnon Møldrup; Halle, Bo; Cédile, Oriane; Burton, Mark; Baun, Christina; Thisgaard, Helge; Anand, Atul; Hubert, Christopher; Thomassen, Mads; Michaelsen, Signe Regner; Olsen, Birgitte Brinkmann; Dahlrot, Rikke Hedegaard; et al.
Abstract: Background: Glioblastomas are highly resistant to therapy, and virtually all patients experience tumor recurrence after standard-of-care treatment. Surgical tumor resection is a cornerstone in glioblastoma therapy, but its impact on cellular phenotypes in the local postsurgical microenvironment has yet to be fully elucidated. Methods: We developed a preclinical orthotopic xenograft tumor resection model in rats with integrated 18 F-FET PET/CT imaging. Primary and recurrent tumors were subject to bulk and single-cell RNA sequencing. Differentially expressed genes and pathways were investigated and validated using tissue specimens from the xenograft model, 23 patients with matched primary/recurrent tumors, and a cohort including 190 glioblastoma patients. Functional investigations were performed in vitro with multiple patient-derived cell cultures. Results: Tumor resection induced microglia/macrophage infiltration, angiogenesis as well as proliferation and upregulation of several stem cell-related genes in recurrent tumor cells. Expression changes of selected genes SOX2, POU3F2, OLIG2, and NOTCH1 were validated at the protein level in xenografts and early recurrent patient tumors. Single-cell transcriptomics revealed the presence of distinct phenotypic cell clusters in recurrent tumors which deviated from clusters found in primary tumors. Recurrent tumors expressed elevated levels of pleiotrophin (PTN), secreted by both tumor cells and tumor-associated microglia/macrophages. Mechanistically, PTN could induce tumor cell proliferation, self-renewal, and the stem cell program. In glioblastoma patients, high PTN expression was associated with poor overall survival and identified as an independent prognostic factor. Conclusion: Surgical tumor resection is an iatrogenic driver of PTN-mediated self-renewal in glioblastoma tumor cells that promotes therapeutic resistance and tumor recurrence.